Optimization of dietary protein to energy level for commercial emu (Dromaius novaehollandiae) production to maximize fat yield - Chamunorwa, Joseph Panashe (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2009.